Pengaruh Strategi Inovasi Terhadap Perkembangan Usaha Mikro Kecil dan Menengah (UMKM) di Desa Pinangsari Kabupaten Subang - Marlinda, Alin; Soleha, Lilis Karnita (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research discusses the innovation strategy for the development of Micro, Small and Medium Enterprises (MSMEs) in Pinangsari Village, Subang Regency. MSMEs have a strategic role in the national economy and contribute to reducing poverty and improving the regional economy. However, MSMEs are faced with various challenges such as limited capital, skills, promotion and market access. Therefore, the implementation of innovative strategies and MSME development is the key in advancing the economy and improving the welfare of the people in Pinangsari Village. The method used is SWOT analysis. Some of the suggested strategies include strengthening training and mentoring, providing capital assistance, developing digital infrastructure, collaboration and partnerships, optimizing digital marketing, and analyzing data for monitoring. By implementing these strategies and adequate support, MSMEs in Pinangsari Village are expected to develop better, become more competitive, and make a greater contribution to the regional economy